Property rights and domestication - Lueck, Dean; Torrens, Gustavo (Journal of institutional economics, 2020)
This paper combines the property rights approach of Barzel with models from renewable resource and evolutionary economics to examine the domestication of wild animals. Wild animals are governed by weak property rights to stocks and individuals while domesticated animals are governed by private ownership of stocks and individuals. The complex evolutionary process of domestication can be viewed as a conversion of wild populations into private property, as well as a transition from natural selection to economic selection controlled by owners of populations and individuals. In our framework domestication is not the explicit goal of any economic agent, but it emerges as a long-run outcome of an innovation in hunting strategies in a hunter–gatherer society. Our formal model also suggests that the domestication process moves slowly at first but then proceeds rapidly, and is aligned with the archeological evidence on domestication events.